Frequency of Rickets in Children with Lower Respiratory Tract Infections Under Five Years of Age - Arshad Karim, Zahid Ullah, Nasir Ayaz (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Rickets is a disease of growing bones which is secondary to the defect in mineralization at growth plate matrix. Vitamin D deficiency remains the most common cause of rickets globally. Vitamin D is usually obtained from exposure to sunlight and from diet like fish liver oil and egg yolk. Solar ultra violet B radiations penetrate the skin and initiate the process of vitamin D formation. Aim: To determine the frequency of nutritional rickets in children with lower respiratory tract infections under five years of age. Methods: It was a cross sectional study conducted in Pediatric Department, Lady Reading Hospital, Peshawar. In this study a total of 151 patients were observed. Children were assessed by researcher by detailed history from the parents followed by detailed clinical examination for the confirmation of lower respiratory tract infections. Blood sample was taken for the children and were send to hospital laboratory for investigation of serum calcium, phosphorus and alkaline phosphatase level. All the laboratory investigations were done by single expert pathologist having minimum of five years of experience and all the radiological findings must be reported by single expert radiologist having minimum of five years of experience. Results: In this study 62% children were in age ranged 1-3 years and 38% children were in age range 4-5 years. Mean age was 2 years with SD ± 2.16. Fifty eight percent children were male and 42% children were females. More over 65% children had low serum calcium level < 2.12 mmol, 58% children had low serum phosphorus level < 0.87 mmol and 60% children had serum alkaline phosphatase > 280 units per liter on the bases of which the frequency of nutritional rickets among 151 children was 60% in our study. Conclusion: Our study concludes that the frequency of nutritional rickets was 60% in children with lower respiratory tract infections under five years of age.